Uses the Disinfectants against fungi isolated from the homes - Al Bahran, Rusol Muhammedi (The Iraqi Journal of Veterinary Medicine, 2011)
The study included 100 samples collected from different locations of the homes were located in the area of Ali Saleh in Baghdad 6 species were isolated from fungi and the most common genus or species of fungi isolated were Aspergillus fumigatus by frequency ratio of 25.84%, and occurrence ratio of 23%, Penicilium by frequency ratio of 21.34%, and occurrence ratio of 19%, Mucor by frequency ratio 20.22%, and the occurrence ratio of 18%, Candida albicans by frequency ratio of 15.73%, the occurrence ratio of 14%, Rhizopus frequency ratio by 13.48%, the occurrence ratio of 12% and Aspergillus niger frequency ratio by 3.37% and the occurrence ratio of 3%. Then the sensitivity test of disinfectants were studied against fungi isolated by using three disinfectants Chloroxylenol known commercially by (Dettol), Chlorhexidine commercially known by (Hibitane) and Sodium hypochlorite commercially known by (Bleach), and a study for the effected of three concentrations of each disinfectant (5, 2.5, 1.25)%, and the use of statistical analysis (ANOVA) to contrast the differences and Dnken test to the variation in any disinfectant or the most efficient concentrations of other disinfectants were observed that concentrations of 5% was the most efficient of concentrations than (2.5%) and (1.25%). As the disinfectant Dettol was significantly the most efficient from Bleach and Hibitane.